Foliar Application of Urea and Amino Acids Regulates Growth, Photosynthesis, Pigments, Antioxidant Activity, and the Essential Oil Content and Composition of Basil (Ocimum basilicum L.) - Saeedeh Jahanbani; Hasan Mumivand; Bahman Zahedi; Sergio Argento (Agronomy)
Basil (Ocimum basilicum L.) is a prominent medicinal and aromatic plant, widely recognized for its bioactive compounds and substantial economic value across the pharmaceutical, culinary, and industrial sectors. In light of increasing global demand and environmental challenges, this study explores novel approaches to enhance its sustainable production and improve its quality. Urea is the most common form of nitrogen (N) for foliar application due to its quick absorption, affordability, high solubility, as well as relatively low cost per N unit. Amino acids are an organic form of N and play a role in plant protein structure, stress tolerance, and the biosynthesis of secondary metabolites. This research aimed to evaluate the effects of urea (0, 1, and 2 g L−1) and an amino acid-based biostimulant (AAB) (0, 4, and 8 mg L−1), applied foliarly, on the growth, photosynthesis, pigments, antioxidant activity, and essential oil production of basil (Ocimum basilicum L.). The best results in terms of leaf number, area, and fresh and dry weight were observed with the combination of 2 g L−1 urea and 8 mg L−1 AAB. The growth enhancement due to this treatment may be attributed to stimulatory effects on photosynthesis and N content. Chlorophyll, carotenoids, anthocyanins, photosynthesis, stomatal conductance, total phenols, and total flavonoids increased with urea application up to 1 g L−1. Additionally, AAB application up to 8 mg L−1 increased total chlorophyll, carotenoid, total phenols, and total flavonoids, while photosynthesis and anthocyanin content increased with 4 mg L−1 AAB. Although urea did not significantly affect essential oil content and yield, AAB application increased both. Finally, the combination of 1 g L−1 urea and 8 mg L−1 AAB had the most effective impact on improving content and yield of essential oil, total phenol, flavonoid, anthocyanin, and antioxidant activity, with a relatively high percentage of estragole.